2019
DOI: 10.31661/jbpe.v0i0.1114
|View full text |Cite
|
Sign up to set email alerts
|

A Monte Carlo Study on the Shielding Properties of a Novel Polyvinyl Alcohol (PVA)/WO3 Composite, Against Gamma Rays, Using the MCNPX Code

Abstract: Background : In recent years, there has been an increased interest toward non-lead radiation shields consisting of small-sized filler particles doped into polymer matrices. In this paper, we study a new polyvinyl alcohol (PVA)/WO3 composite in the presence of high-energy gamma photons through simulation via the Monte Carlo N-Particle (MCNP) simulation code.Materials and Methods: An MCNP geometry was first designed in the software based on real-life conditions, and the generated geometry was validated by calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…Bismuth nanoparticles with cellulose nanofibers and polydimethylsiloxane (PDMS) polymer can effectively shield X-ray radiation at a lower mass ratio in the polymer matrix (Li et al 2018 ). Novel polyvinyl alcohol (PVA)/tungsten oxide (WO 3 ) composite consisting tungsten oxide (WO 3 ) at sizes of 10 μm and 30 nm with a weight concentration of 50 weight % was studied for gamma-ray shielding (Kazemi et al 2019 ).…”
Section: Polymer Composites For Gamma-radiation Shieldingmentioning
confidence: 99%
“…Bismuth nanoparticles with cellulose nanofibers and polydimethylsiloxane (PDMS) polymer can effectively shield X-ray radiation at a lower mass ratio in the polymer matrix (Li et al 2018 ). Novel polyvinyl alcohol (PVA)/tungsten oxide (WO 3 ) composite consisting tungsten oxide (WO 3 ) at sizes of 10 μm and 30 nm with a weight concentration of 50 weight % was studied for gamma-ray shielding (Kazemi et al 2019 ).…”
Section: Polymer Composites For Gamma-radiation Shieldingmentioning
confidence: 99%
“…Kazemi et al studied new polyvinyl alcohol (PVA)/WO 3 composite in the presence of high-energy gamma photons through simulation via the Monte Carlo N-Particle (MCNP) simulation code. They found that the PVA/WO 3 composite can be considered as a shield for the gamma energy at the level of 662, 778, 964, 1112, 1170, 1130, and 1407 keV 18 . Later, Atashi et al fabricated a flexible silicone rubber/W/Bi 2 O 3 by an open mold cast technique 19 .…”
Section: Introductionmentioning
confidence: 99%
“…It was established that the nanoscale reinforced HDPE enhanced the overall shielding properties, particularly at lower photon energies. Another study was conducted on a new polyvinyl alcohol (PVA)/WO 3 composite based on the Monte Carlo N-Particle (MCNP) simulation code [ 26 ]. It was noted that the PVA/WO 3 composite could be considered as a shield for photon energy at the levels of 662, 778, 964, 1112, 1170, 1130, and 1407 keV.…”
Section: Introductionmentioning
confidence: 99%